(untitled) (American Journal of Islam and Society, 2010)
This work of historical theology is essential reading for those wanting to understand with new depth and clarity the life and teachings of al-Ghazali (d. 505/1111). It is sometimes maintained that he contributed significantly to Muslim scholars’ ending of scientific inquiry and the use of reason. This view has recently been promoted afresh by Robert Reilly’s The Closing of the Muslim Mind (Wilmington, DE: 2010). Griffel extensively discusses two factors contributing to this general perception: al-Ghazali’s opposition to the philosophers in Tahafut al-Falasifah (see M. Marmura, ed and tr. The Incoherence of the Philosophers [Provo, UT: 1997]) and his endorsement of occasionalism, the idea that events do not occur because of their inherent properties, such as fire’s ability to burn cotton, but instead God creates each individual event with no reference to causes and effects in the physical world. Thus there is, at least in theory, no predictable causality in the world. This would seem to render scientific inquiry, which relies on predictable processes, theoretically impossible. Scholars have differed over whether al- Ghazali is indeed an occasionalist (Marmura) or in fact endorses causality in line with the philosopher Ibn Sina (Richard Frank). In contrast, Griffel sets out to demonstrate that al-Ghazali “is the first Muslim theologian who actively promotes the naturalization of the philosophical tradition into Islamic theology” (p. 7) and that his writings are ‘a particular kind of Avicennism’ (p. 14). His central argument is that al- Ghazali remained uncommitted throughout his career as to whether God brings about events in this world through occasionalism or via secondary causality. Griffel contends that his consistent position was to regard each position as possible, developing “something like a synthetic position between these two poles” (p. 12). In arguing for this, the author presents a highly persuasive reading of al-Ghazali’s principal texts, which presents him as avoiding self-contradiction on this issue ...